Firm performance and family related directors: Empirical evidence from an emerging market - Hafezali, I. H.; Azlan, A.; Mohd Thas Thaker, Hassanudin *; Mohsin, A. (University of Economics and Human Sciences in Warsaw, 2019)
Board composition is central to the worldwide corporate governance reforms that have taken place in recent years. The strong emphasis on director independence and board leadership is now part of all corporate governance regimes, including the regimes which has been introduced in Malaysia. It is the effectiveness of such provisions in the Malaysian business environment that provides the motivation for this paper. The literature shows mixed findings on the issues of board independence and board leadership. Our paper studies the role of directors with family connections and its impact on financial outcomes. We find that firms with a high presence of family related directors exhibit superior accounting profitability. However, such dominance is negatively viewed by the market (firm performance based on market measures), indicating that markets tend to perceive that domination of family members on the board could potentially lead to expropriation of wealth at the expense of other shareholders. Our results are supported by additional robustness tests. The findings provide interesting insights into the governance mechanisms of firms in an emerging market and its consequences for investor perceptions. Further implications are also discussed.